Encephalitis or Stroke? A Case Report of Thalamic Stroke in COVID Era - Anandi Damodaran; Rim Koutaich; Devdutt Nayak; Imad Hamad; Rajesh Gupta; Mohammad Ibrahim (Dubai Medical Journal)
Introduction: Since 2019, COVID-19 pneumonia caused by SARS-CoV-2 virus has led to a worldwide pandemic. Since then, various neurological manifestations of COVID-19 pneumonia have been reported. Neurological manifestations include headache, anosmia, seizures, and altered mental status. In some cases, it presents as stroke, encephalitis, and neuropathy. Artery of Percheron (AOP) is a variant in the posterior circulation. Here, a single artery arises from the posterior cerebral artery p1 segment. It supplies bilateral thalamus with or without midbrain. Thrombosis in this artery leads to clinical symptoms like reduced level of consciousness, altered mental status, and memory impairment. Case Report: Here, we present a case who presented with fever and altered sensorium without any focal neurological deficits and without known risk factors for stroke. His COVID-19 PCR was positive. He was initially diagnosed as COVID-19 pneumonia with encephalitis and was started on treatment for the same. His initial CT brain and lumbar puncture were normal. The next day, when MRI brain with and without contrast was done, the thalamic stroke due to AOP infarction was diagnosed and appropriate treatment for stroke was initiated. Discussion: Many patients miss the window for thrombolysis because of variable presentation in clinical symptoms with negative imaging. It is also difficult to assess the time of onset of stroke in this varied presentation. Our patient had fever and cough for 2 days and had altered mental status since the morning of admission. During hospital stay, he developed bilateral third nerve palsy. This case also highlights the importance of detailed evaluation in COVID-19 patients with neurological complaints. This helps to avoid delays in treatment and to improve clinical outcomes. As our knowledge of COVID-19 and its varied neurological manifestations evolve, we need to be prepared for more atypical presentation to facilitate timely interventions.